The Impacts of Blue Stain Degradation on the Industrial Processing Properties of logs - Osman Komut; Atakan Öztürk (Doğal Afetler ve Çevre Dergisi)
Blue staining leads to significant economic losses because of the changes it causes in the aesthetic characteristics and mechanical shock resistance of log, timber and materials in the usage area. On the other hand, it is known that the low success rate of impregnation and surface treatment in materials exposed to degradation considerably narrows down industrial usage areas of the logs. This study aims to determine the effects of blue stain degradation on manufacturing process of forest industry managements processing log and the losses caused by this. This research was conducted in a total of 9 small and medium sized lumber production managements processing scots pine log in Gümüşhane province. In this study, the size of the blue stain degradation was evaluated by calculating the total volume of the log. On the other hand, comparisons regarding blue stain degradation have been carried out between the managements that conduct productions intended for the construction and woodworking sectors. At the end of the study, it has been determined that the ratio of exposure to volumetric damages ranges between %32-84 depending on fresh wood width, log length and diameter variables in the blue stain degradation. Furthermore, it has been confirmed that statistically significant differences (p<0.05) exist between the blue stained area in corrupted volume ratio and the cross-section horizontal to the log variables between managements manufacturing for the construction and woodworking sectors. On the other hand, it has been observed that blue stain degradation is overlooked in timber manufacturers producing for the construction sector. In the managements manufacturing for the woodworking sector, it has been identified that the blue stained part is removed to improve the visual qualities of the material, however, additional energy and workforce costs originate because of this process.